2012
DOI: 10.1016/j.ssci.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the impairment profiles of older drivers and non-drivers: Toward the development of a fitness-to-drive model

Abstract: The purpose of this research effort was to compare older driver and non-driver functional impairment profiles across some 60 assessment metrics in an initial effort to contribute to the development of fitness-to-drive assessment models. Of the metrics evaluated, 21 showed statistically significant differences, almost all favoring the drivers. Also, it was shown that a logistic regression model comprised of five of the assessment scores could completely and accurately separate the two groups. The results of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Consistent with some prior work (44), changes in physical function were positively related to driving behavior trajectories, after controlling for demographics, baseline cognitive function and visual acuity, attrition, and changes in general health. Specifically, changes in grip strength were associated with changes in driving space and number of miles driven in an average week, while changes in the number of steps and self-reported physical function were positively associated with driving exposure and driving frequency changes.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Consistent with some prior work (44), changes in physical function were positively related to driving behavior trajectories, after controlling for demographics, baseline cognitive function and visual acuity, attrition, and changes in general health. Specifically, changes in grip strength were associated with changes in driving space and number of miles driven in an average week, while changes in the number of steps and self-reported physical function were positively associated with driving exposure and driving frequency changes.…”
Section: Discussionsupporting
confidence: 81%
“…First, only three physical functioning measures are available in the ACTIVE data set. Numerous physical functioning measures with variable levels of standardization, reliability, and validity are available, some of which may be more sensitive indicators of physical functioning as related to driving mobility; for example, time to reach peak force production at the ankle joint (44). An additional potential limitation is that driving mobility indices were self-reported and may not necessarily accurately capture true driving habits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies have investigated the relationship between physical limitations and fitness-to-drive (Reimer, D'Ambrosio et al 2008;Antin, Lockhart et al 2012). A study by Antin compared 49 drivers and non-drivers 65 years of age and older on various physical and mental assessments (Antin, Lockhart et al 2012). Results showed that non-drivers had more physical and cognitive limitations than those who continued to drive (Antin, Lockhart et al 2012).…”
Section: Physical Limitations and Fitness-to-drivementioning
confidence: 99%